Twelve months of oral ulceration, weight loss and unexplained fevers: a clinicopathologic conference. (20th January 2019) - O'Sullivan, L.; Galvin, S.; Flavin, R.; Fadalla, K.; Healy, C.M.; Feeney, E.
Abstract: Extranodal NK/T‐cell lymphoma (ENKL) is a rare, aggressive form of non‐Hodgkin's lymphoma with a distinct ethnic predilection favouring populations from Asia and Central and South America. The nasopharynx is the most commonly affected anatomical site. One of the key markers of this disease entity is infection with Epstein‐Barr virus (EBV), which is detected by in situ hybridisation. Histopathology and immunohistochemistry play a vital role in the diagnostic process, with cells typically expressing CD56, TIA‐1 and CD3ε. We present here a very unusual case of ENKL in a Caucasian female with an extranasal presentation, absence of CD56 expression and presence of EBV‐positive cells in the bone marrow. The unusual presentation of the disease in this case, as well as the many diagnostic challenges encountered, are detailed in this paper. It is hoped that this case will prompt clinicians to consider the possibility of an underlying malignant process in cases of refractory oral ulceration with concurrent clinical signs and symptoms.